Vertiginous life an anthropology of time and the unforeseen - Knight, Daniel M. (Berghahn Books, 2021)
Vertiginous Life provides a theory of the intense temporal disorientation brought about by life in crisis. In the whirlpool of unforeseen social change, people experience confusion as to where and when they belong on timelines of previously unquestioned pasts and futures. Through individual stories from crisis Greece, this book explores the everyday affects of vertigo: nausea, dizziness, breathlessness, the sense of falling, and unknowingness of Self. Being lost in time, caught in the spin-cycle of crisis, people reflect on belonging to modern Europe, neoliberal promises of accumulation, defeated futures, and the existential dilemmas of life held captive in the uncanny elsewhen
Description based on online resource; title from PDF title page (publisher's Web site, viewed 04. Okt 2022)
Keywords: SOCIAL SCIENCE / Anthropology / Cultural & Social; Crises -- Greece -- Psychological aspects; Time perception -- Social aspects -- Greece; Vertigo -- Greece